Molecular dynamics simulation of the nonlinear behavior of the CNT-reinforced calcium silicate hydrate (C–S–H) composite. (March 2016) - Eftekhari, Mehdi; Mohammadi, Soheil
Abstract: Calcium–Silicate–Hydrate (C–S–H), which is the major constituent of the cement at the nanoscale, is responsible for the strength and fracture properties of concrete. This research is dedicated to the numerical study of enhanced mechanical properties of C–S–H reinforced by embedding carbon nanotube (CNT) in its molecular structure. Series of molecular dynamics (MD) simulations indicate that the tensile strength of CNT-reinforced C–S–H is substantially enhanced along the direction of CNT as compared to the pure C–S–H. The results of tensile loading reveal that CNT can efficiently bridge the two sides of cracked C–S–H. In addition, CNTs can severely intensify the "transversely isotropic" response of the CNT-reinforced C–S–H. Furthermore, the pull-out behavior of CNT reveals that the force-displacement response can be estimated by a bilinear model, which can later be used for simulation of cohesive crack propagation and multiscale simulation of crack bridging at macro scale specimen of CNT-reinforced cement.